2013
DOI: 10.1104/pp.113.228213
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence-Ready Physical Map of Barley Anchored Genetically by Two Million Single-Nucleotide Polymorphisms    

Abstract: Barley (Hordeum vulgare) is an important cereal crop and a model species for Triticeae genomics. To lay the foundation for hierarchical map-based sequencing, a genome-wide physical map of its large and complex 5.1 billion-bp genome was constructed by high-information content fingerprinting of almost 600,000 bacterial artificial chromosomes representing 14-fold haploid genome coverage. The resultant physical map comprises 9,265 contigs with a cumulative size of 4.9 Gb representing 96% of the physical length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 60 publications
0
76
0
1
Order By: Relevance
“…Two additional features facilitated HvLax-a identification: the target gene was included in the target enrichment assay, and the mode of mutagenesis resulted in complete deletion of the functional gene. As the barley genome sequence was largely an unordered draft (Mayer et al, 2012;Ariyadasa et al, 2014), our initial genetic analysis revealed a large physical region of the chromosome represented by highly fragmented sequence information that required a substantial amount of further work to fully resolve. In the near future, the cloning of genes in the nonrecombining part of barley chromosomes will become much more efficient, given the impending release of a highly improved physical map-based reference sequence.…”
Section: Natural Diversity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional features facilitated HvLax-a identification: the target gene was included in the target enrichment assay, and the mode of mutagenesis resulted in complete deletion of the functional gene. As the barley genome sequence was largely an unordered draft (Mayer et al, 2012;Ariyadasa et al, 2014), our initial genetic analysis revealed a large physical region of the chromosome represented by highly fragmented sequence information that required a substantial amount of further work to fully resolve. In the near future, the cloning of genes in the nonrecombining part of barley chromosomes will become much more efficient, given the impending release of a highly improved physical map-based reference sequence.…”
Section: Natural Diversity Analysismentioning
confidence: 99%
“…As the WGS contig bearing the candidate gene was not linked to the barley physical map, the candidate gene MLOC_61451.6 was used to PCR screen a barley BAC library, and four clones (HVVMRXALLeA0046E04, HVVMRXALLeA0122D17, HVVMRXALLeA0209O12, and HVVMRXALLeA0379H14), all belonging to the same BAC contig (FPC_2862) of the physical map (Ariyadasa et al, 2014), were identified. A minimum tiling path of overlapping nonredundant BAC clones, spanning the complete FPC_2862, was shotgun sequenced and de novo assembled, yielding 2.3 Mb of unique sequence (Supplemental Table S6).…”
Section: Mapping-by-sequencing Of Pooled Recombinant Plants Revealed mentioning
confidence: 99%
“…The unexpected results might be due to the limited resolution of the current barley physical map while the non-coding region may play a key role in inducing semi-dwarfness. Owing to the large size of the barley genome (5.1 Gb) and the high repeat content (80 %), the current physical map comprises 9,265 contigs with a cumulative size of 4.9 Gb representing 96 % of the physical length of the barley genome [70]. Chromosomal assignments between the POPSEQ and IBSC maps agree in 97.6 % of the cases and discordant contig placements mostly occurred in the genetic centromere due to the severely reduced recombination frequency [55, 68].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the map-based cloned barley genes have been located in the distal regions of the chromosome. Considering that ari-e occurred near the centromere of barley 5H [25], the repetitive nature of the barley genome [55, 70, 71] and limited resolution of the barley physical map, there may be other unanchored candidate genes for the ari-e semi-dwarf gene.…”
Section: Discussionmentioning
confidence: 99%
“…Availability of barley genome reference sequence [17] facilitates application of WGS-based approaches (such as RNA-seq) for investigating genetic networks responsible for phenotypic variation. RNA-seq approach has been already employed successfully to uncover the history of wild barley domestication and distribution [18], for studying the gene family of barley aquaporines [19] or creating SNP maps of barley [20]. …”
Section: Introductionmentioning
confidence: 99%